2015
DOI: 10.1016/j.aej.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and parametric studies of a louvered fin and flat tube compact heat exchanger using computational fluid dynamics

Abstract: The present study aimed to perform the parametric analysis on thermo-hydraulic performance of a compact heat exchanger using computational fluid dynamics (CFD). The analysis has been carried out at different frontal air velocities by varying the geometrical parameters such as fin pitch, transverse tube pitch, longitudinal tube pitch, louver pitch and louver angle. The air side performance of the heat exchanger has been evaluated by calculating Colburn factor (j) and Fanning friction factor (f). The comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…They showed the existence of frequency components in the flow behind a fully-developed louver. By varying the geometrical parameters, Karthik et al [8] performed experimental and parametric analyses in order to study the thermo hydraulic performance of a compact heat exchanger with louvered fins. They showed that the increase in both the transverse and longitudinal tube pitches can lead to a higher pressure drop at un-louvered fin surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…They showed the existence of frequency components in the flow behind a fully-developed louver. By varying the geometrical parameters, Karthik et al [8] performed experimental and parametric analyses in order to study the thermo hydraulic performance of a compact heat exchanger with louvered fins. They showed that the increase in both the transverse and longitudinal tube pitches can lead to a higher pressure drop at un-louvered fin surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…If the Q max value is defined as the maximum possible heat transition, it can be written as follows, provided that it is smaller than the C h or C c thermal capacity outputs [14,15]:…”
Section: Thermodynamic Analysis Of Plate Heat Exchangersmentioning
confidence: 99%
“…Figure 18. Variation of the heat transfer coefficient with respect to the frontal velocity for different (a) tube pitches (F p = 1.5 mm, L p = 1.2 mm, L α =26 o ) and (b) fin pitches (T p = 9.6 mm, L p = 1.2 mm, L α =26 o ) [25]. Figure 19.…”
Section: Performance Evaluation Criteria Of the Louvered Fin Heat Excmentioning
confidence: 99%